Analisis Strategi Komunikasi dalam Mempertahankan Relasi Bisnis Jangka Panjang di Suara Merdeka Generation - Dhika Gamaliel Arisandy; Heri Pamungkas (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze the implementation of communication strategies carried out by Suara Merdeka Generation (SMGen) as an Event Organizer in maintaining long-term business relationships with clients, as well as to identify the challenges that arise in practice amidst the increasingly complex dynamics of the event industry. This research employs a qualitative descriptive approach through in-depth interviews, observation, and documentation involving internal parties directly engaged in event management. The findings reveal that SMGen’s communication strategy has been systematically implemented through stages of analysis, goal formulation, message development, media selection, two-way communication, and evaluation, supported by the utilization of digital media and adaptive approaches to client characteristics. These strategies are not only focused on the success of event execution but are also directed toward sustaining long-term collaboration with clients through continuous and value-added communication. However, the implementation still faces several challenges, particularly in terms of the consistency of communication transparency, internal coordination, and the dynamic changes in client needs that are not always communicated optimally. The findings indicate that communication transparency plays a strategic role in maintaining client trust and loyalty as the foundation of long-term business relationships, through openness of information, clarity of messages, and consistency in communication.